Pembuatan tool pemodelan eksperimen gerak parabola dengan pengaturan sudut elevasi untuk analisis video tracker (Experimental modeling tools fabrication for parabolic motion with elevation angle settings for video tracker analysis) - Atika Irbah; - Asrizal (PILLAR OF PHYSICS, 2019)
Physics has an important role in the development of Science and Technology. One interesting phenomenon of motion in physics, namely parabolic motion. The importance of the parabolic motion instrument is to understand various types of parabolic motion concepts. From the result of observation, it was known that the parabolic motion experiment was still done manually, namely the measured physical quantities were limited and It can’t display the graph. Experimental tools have weaknesses in parabolic motion experiment activities because they weren’t effective when used. One solution to overcome this weakness is developing a tracker video analysis and modeling tool. The purpose of this research is to determine the performance specifications of a parabolic experiment modeling tool, the design specifications of a parabolic experiment modeling tool, and the effect of the elevation angle change of a parabolic experiment modeling tool. This research can be classified into engineering research method, namely a research method to design a process, product or prototype to make a new contribution. Data collection is done in two ways, namely directly and indirectly measurement. Direct measurement is done by varying the level of the launcher angle in the parabolic motion experiment modeling tool. Indirect measurement is used to determine the accuracy and precision of the parabolic motion experiment modeling tool. Data of the measurement results were analyzed with descriptive statistics in the form of graphs and tables. Based on data analysis, it can be stated that there are three research results. First, the main performance specifications of the parabolic motion experiment modeling tools include: the tool frame size is 14x15x22.5 cm3 and the regulator of elevation angle is done by using the MG995 servo motor. Second, the average accuracy of the experimental results of the modeling tool is 97.38%, while the its average accuracy is 98.59%. Third, the change in elevation angle influences on the time to reach the peak point, maximum height, and time when reaching the maximum distance. The greater the elevation angle causes the value of the time to reach peak point, the maximum height value, and the time to reach the maximum distance also greater. The elevation angle also affects to the maximum distance. From the result of the analysis, it can be confirmed that the maximum distance is obtained when the elevation angle is 45o.